2020
DOI: 10.3390/jmse8110938
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Trajectory and Biomass Growth of Free-Floating Macroalgal Cultivation Platforms along the U.S. West Coast

Abstract: Trajectory tracking and macroalgal growth models were coupled to support a novel macroalgae-harvesting concept known as the Nautical Off-shore Macroalgal Autonomous Device (NOMAD). The NOMAD consists of 5 km long carbon-fiber longlines that are seeded and free float southward along the U.S. West Coast for approximately 3 months before harvesting off the California coast, taking advantage of favorable environmental conditions. The trajectory and macroalgal growth models were applied to answer planning questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Here, we use a growth model for S. latissima (sugar kelp) first proposed by Broch and Slagstad (2012). This species was chosen because it is relatively well-studied due to its widespread use in aquaculture and it has been proposed as a candidate for offshore macroalgae farms (Broch et al, 2019;Whiting et al, 2020;Running Tide, 2021). Although other models for S. latissima have been developed (e.g., Venolia et al, 2020), we use the model first described in Broch and Slagstad (2012) because it has been tested in North Atlantic conditions (Broch and Slagstad, 2012;Broch et al, 2013Broch et al, , 2019Molen et al, 2018) and its inputs (temperature, nitrate concentration, and irradiance) are readily available from ocean state estimates and reanalysis products.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we use a growth model for S. latissima (sugar kelp) first proposed by Broch and Slagstad (2012). This species was chosen because it is relatively well-studied due to its widespread use in aquaculture and it has been proposed as a candidate for offshore macroalgae farms (Broch et al, 2019;Whiting et al, 2020;Running Tide, 2021). Although other models for S. latissima have been developed (e.g., Venolia et al, 2020), we use the model first described in Broch and Slagstad (2012) because it has been tested in North Atlantic conditions (Broch and Slagstad, 2012;Broch et al, 2013Broch et al, , 2019Molen et al, 2018) and its inputs (temperature, nitrate concentration, and irradiance) are readily available from ocean state estimates and reanalysis products.…”
Section: Modelmentioning
confidence: 99%
“…One CDR strategy that has been proposed is the growth of benthic macroalgae on artificial substrates in the open ocean, away from their native habitat (rocky bottomed coastal waters). For example, Whiting et al (2020) modeled kelp growth on free-floating platforms off the West Coast of the United States. Although they did not consider the influence of macroalgae on phytoplankton or the carbon cycle, they found that this strategy could yield significant macroalgal biomass at the end of a 3 month deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Affected by the thickness of clouds, irradiation intensity at noon fluctuated The surface salinity of the south YS fluctuated between 29 and 33 PSU during the period of the green tide bloom (Figs. 5i and j and 6i and j), which was suitable for U. prolifera growth (Xiao et al, 2016). For this reason, the salinity limitation was ignored in the biological module.…”
Section: Irradiation and Salinitymentioning
confidence: 99%
“…The biomass, growth, and spatial coverage of the floating macroalgae change dynamically over time, which can be simulated by a biogeochemical and ecosystem model (Lovato et al, 2013;Perrot et al, 2014;Sun et al, 2020). The growth and mortality are controlled by changing environmental factors, such as temperature, light intensity, salinity, dissolved nutrients, dissolved oxygen, seawater turbidity, and predation by zooplankton (Cui et al, 2015;Shi et al, 2015;Xiao et al, 2016). Incorporating physical drifting models and the biogeochemical growth model appears essential to high-precision simulation (Brooks et al, 2018).…”
Section: Introductionmentioning
confidence: 99%